AB0835-HPR Evaluating the impact of a specialist ankylosing spondylitis rehabilitation programme on patient's quality of life. (23rd January 2014) - O'Shea, D. J.; Thomas, A.; Turner-Cobb, J.; Hill, I.; Clarke, E.; Groves, S.; France, B.; Sengupta, R.
Abstract : Background: Traditionally the effectiveness of rehabilitation programmes has been determined using physical/functional outcomes. However, given that the goals of rehabilitative interventions extend beyond medical outcomes, it is imperative to report and interpret the results of these measures (Ditewig, Blok, Havers, & van Veenendaal, 2010). As such, the current study which investigates the impact the RNHRD in-patient programme has on individual's QoL, represents a timely evaluation of an important indicator of the programme's effectiveness. Objectives: To evaluate the RNHRD in-patient programme by testing the hypothesis that individual's would demonstrate improvements in QoL following the programme. The secondary objective is concerned with predicting which patients would derive the most benefit from the programme, in terms of QoL. Methods: The evaluation utilized existing data gathered from the 2011 cohort of patients ( N = 153). QoL was measured using the ASQoL (Doward et al., 2003). To test the primary hypothesis a one sample t-test was conducted. Subsequently, to assess whether certain variables including: age, gender, anti-TNF, employment status, course intensity, number of previous courses, disease duration, delay in diagnosis could predict changes in patients QoL, a standard multiple regression analysis was conducted. Results: The primary hypothesis was supported: statistically significant improvements in QoL scores were observed following the two-week programme; p = .001 (one-tailed), d = .57; 95% CI [2.79, -1.57]. The results of the exploratory analysis indicated that individual's baseline measure of QoL and course intensity significantly predict change in ASQoL scores following the programme; (B) = -.417, p = .001, 95% CI [-.559 – -275]; (B) = 2.107, p = .043, 95% CI [.069 – 4.145] respectively. Conclusions: The results of current evaluation build upon previous research purporting the effectiveness of the RNHRD in-patient programme (Band, Jones, & Kennedy, 1997; Dale, 2011). In combination these studies provide increasing evidence for the effectiveness of the RNHRD in-patient programme in terms of improved physical functioning, patient satisfaction and QoL. References: Band, D., Jones, S., & Kennedy, L. (1997). Which patients with ankylosing spondylitis derive most benefit from an inpatient management program? Journal of Rheumatology, 24 (12), 2381–2384. Dale, R. (2011). An evaluation of patients' perspectives of participation in a two-week residential hospital based Ankylosing Spondylitis rehabilitation programme (Unpublished master's thesis) . University of Bath. Ditewig, J. B., Blok, H., Havers, J., & van Veenendaal, H. (2010). Effectiveness of self-management interventions on mortality, hospital readmissions, chronic heart failure hospitalization rate and quality of life in patients with chronic heart failure: a systematic review. Patient education and counseling, 78 (3), 297–315. Doward, L. C., Spoorenberg, A, Cook, S. A, Whalley, D., Helliwell, P. S., Kay, L. J., McKenna, S. P., et al. (2003). Development of the ASQoL: a quality of life instrument specific to ankylosing spondylitis. Annals of the rheumatic diseases, 62 (1), 20–6. Disclosure of Interest: None Declared